Project management and Six Sigma: obtaining a fit. (22nd May 2008) - Wright, J. Nevan; Basu, Ron
Six Sigma is a holistic approach to achieving near perfection, expressed in terms of no more than 3.4 errors per million opportunities. This near perfection appears to many to be overkill or to some, an impossible ideal. Nonetheless, Six Sigma has been adopted by many leading companies. The benefits are well documented for manufacturing industries and increasingly, in service industries. This paper shows how the philosophy of Six Sigma can be made to 'fit' to project management. The benefits for project managers will be better (less painful) management, less overruns in time and budget and finally, happier clients. This paper is drawn from Basu and Wright's (2003) Quality Beyond Six Sigma and includes material presented by the author at the World Congress Total Quality Management (2006).